Glucose-fructose enhances performance versus isocaloric, but not moderate, glucose - Baur, D. A.; Schroer, A. B.; Luden, N. D.; Womack, C. J.; Smyth, S. A.; Saunders, M. J. (Medicine & Science in Sports & Exercise, 2014)
Purpose: The effects of glucose-and-fructose (GF) coingestion on cycling time trial (TT) performance and physiological responses to exercise were examined under postprandial conditions.